Enhanced protein degradation by intracellular delivery of pre-fused PROTACs using lipid-like nanoparticles - Chen, Jinjin; Qiu, Min; Ma, Feihe; Yang, Liu; Glass, Zachary; Xu, Qiaobing (Journal of controlled release, 2021)
Proteolysis-targeting chimaera (PROTAC) technology is an emerging approach for achieving targeted degradation of a protein of interest (POI) intracellularly. However, the cell permeability of PROTACs is limited by their high molecular weight and total polar surface area. Moreover, the activation of the proteasome-mediated degradation by PROTAC requires the formation of a ternary (three-component) complex, composed of the PROTAC, the POIs, and E3-ligases related proteins (E3Ps). Simplifying the three-component system to two-component system could theoretically increase the efficiency of the formation of ternary complex and enhance the protein degradation efficiency. Herein, we demonstrate that pre-fusion of PROTACs with E3Ps (called “pre-fused PROTACs”) before administration could transform the original PROTAC system to two-component system. After delivery by lipid nanoparticles, the degradation of POI by pre-fused PROTACs was dramatically increased and accelerated compared with standard PROTACs. Moreover, we demonstrated that this approach could be generalized to another hydrophobic tag (HyT) degrader by demonstrating the improved targeted protein degradation after pre-fusion the HyT degrader with heat shock protein 70 (HSP70). [Display omitted] •Pre-fused PROTACs conveted three component PROTACs to two component systems•Pre-fused ARV-771 delivered by 80-O14B enhanced the degradation of BRD4•Pre-fusion was proved to be a general method for enhancment of protein degradation